Characterization of a spermidine hydroxycinnamoyltransferase in Malus domestica highlights the evolutionary conservation of trihydroxycinnamoyl spermidines in pollen coat of core Eudicotyledons - Elejalde-Palmett, Carolina; de Bernonville, Thomas Dugé; Glevarec, Gaëlle; Pichon, Olivier; Papon, Nicolas; Courdavault, Vincent; St-Pierre, Benoit; Giglioli-Guivarc’h, Nathalie; Lanoue, Arnaud; Besseau, Sébastien (Journal of experimental botany, 2015)
Phenolamides, so called hydroxycinnamic acid amides, are specialized metabolites produced in higher plants, involved in development, reproduction and serve as defence compounds in biotic interactions. Among them, trihydroxycinnamoyl spermidine derivatives were initially found to be synthetized by a spermidine hydroxycinnamoyltransferase (AtSHT) in Arabidopsis thaliana and to accumulate in the pollen coat. This study reports the identification, in Malus domestica, of an acyltransferase able to complement the sht mutant of Arabidopsis. The quantitative RT-PCR expression profile of MdSHT reveals a specific expression in flowers coordinated with anther development and tapetum cell activities. Three phenolamides including N¹, N⁵, N10-tricoumaroyl spermidine and N¹, N⁵-dicoumaroyl-N10-caffeoyl spermidine identified by LC/MS, were shown to accumulate specifically in pollen grain coat of apple tree. Moreover, in vitro biochemical characterization confirmed MdSHT capacity to synthesize tri-substituted spermidine derivatives with a substrate specificity restricted to p-coumaroyl-CoA and caffeoyl-CoA as an acyl donor. Further investigations of the presence of tri-substituted hydroxycinnamoyl spermidine conjugates in higher plants were performed by targeted metabolic analyses in pollens coupled with bioinformatic analyses of putative SHT orthologues in a wide range of available plant genomes. This work highlights a probable early evolutionary appearance in the common ancestral core Eudicotyledons of a novel enzyme from the BAHD acyltransferase superfamily, dedicated to the synthesis of trihydroxycinnamoyl spermidines in pollen coat. This pathway was maintained in most species; however, recent evolutionary divergences have appeared among Eudicotyledons, such as an organ reallocation of SHT gene expression in Fabales and a loss of SHT in Malvales and Cucurbitales.